Switzerland : Financial Sector Assessment Program; Factual Update; Basel Core Principles for Effective Banking Supervision. (IMF Staff Country Reports; Country Report ;, 2007)
This technical note presents a factual update of the 2001 assessment of Switzerland's compliance with the 1997 Basel Core Principles for Effective Banking Supervision (BCP), including a follow-up on implementation of the 2001 BCP assessment, undertaken in the context of the original Financial Sector Assessment Program in 2001. The note discusses that the Swiss Federal Banking Commission (SFBC) has made impressive progress both organizationally and to its supervisory practices to strengthen Switzerland's banking supervisory framework. The SFBC has also significantly improved its outreach to foreign supervisors and its collaboration with external auditors and the industry.